2011
DOI: 10.1016/j.bcp.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

DNA interactions of 2-pyrrolinodoxorubicin, a distinctively more potent daunosamine-modified analogue of doxorubicin

Abstract: It was shown earlier that 2-pyrrolinodoxorubicin was 500-1000 times more active towards human and mouse cancer cells in vitro than parental doxorubicin. However, the biochemical factors responsible for such a large difference in potency between doxorubicin and 2-pyrrolinodoxorubicin are not clear at the molecular level. To provide this information, we have investigated in cell-free media by biochemical and biophysical methods interactions of both anthracyclines with DNA, effects of these interactions on activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Thus, it is feasible to covalently bind the amino group with carboxyl groups to form a stable amide bond. In addition, studies have shown that modification of the primary amino group could greatly reduce the cardiotoxicity, which is one of the main objectives to modify ADM (16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is feasible to covalently bind the amino group with carboxyl groups to form a stable amide bond. In addition, studies have shown that modification of the primary amino group could greatly reduce the cardiotoxicity, which is one of the main objectives to modify ADM (16).…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin is another useful wide-spectrum anticancer drug with a mechanism of action distinct from that of mitomycin C (14). Doxorubicin efficiently intercalates between DNA bases, and a ternary drug-DNA-topoisomerase II 'cleavable complex' (15,16) is subsequently formed. Such structural changes ultimately inactivate topoisomerase, and excision and rejoining of the damaged region cannot proceed (17).…”
Section: Introductionmentioning
confidence: 99%
“…Some molecules like doxorubicin [86,87] and related molecules [88,89] can intercalate into the double strand of DNA and are typically available for biological interactions only after DNA is degraded. Other strategies aim at immobilizing BAM while simultaneously making them available for interaction with the surrounding biological system without necessitating DNA degradation; these are the methods that the following chapters will focus on.…”
Section: Bringing Biologically Active Molecules Into the Gamementioning
confidence: 99%